'He's got growth': Coaches understanding and management of the growth spurt in male academy football. Issue 1 (February 2023) - Hill, Megan; John, Thomas; McGee, Darragh; Cumming, Sean P.
The majority of studies investigating maturation in football have focused on the impact of maturity status or timing upon athletic performance. There is comparatively little research investigating the impact of the adolescent growth spurt, and few research articles that have focussed on injury incidence and burden rather than performance. The aim of this study was to explore and better understand how the adolescent growth spurt impacts youth football players within professional academies. This longitudinal mixed-methods study aimed to understand youth football coaches' perceptions, experiences, and management of male adolescent football players. Players' maturity status, growth velocities, and match performance were measured and interviews with coaches were conducted in parallel. The qualitative and quantitative data were combined to generate a deeper contextualised understanding. This study revealed that academy football coaches describe adolescent growth as a 'condition'; players are diagnosed with growth through perceived signs and symptoms, which coaches must manage and treat. Growth was also seen to impact coaches' perceptions and therefore had implications for selection and release decisions. The findings from this study emphasise the complexities of experiencing and managing adolescent growth and maturation in the context of elite youth football.